Experimental response of HPFL-BSP strengthened RC sub-assemblages subject to corner column removal - Huang, Min; Huang, Hua; Qian, Kai; Li, Jinru; Guo, Mengxue (Journal of Building Engineering, 2024)
Few existing buildings have been constructed in accordance with progressive collapse codes, resulting in poor progressive collapse behavior. Previous studies indicated that reinforced concrete (RC) structures with one lost corner column are more susceptible to progressive collapse than structures that lose a middle or edge column. To mitigate the likelihood of progressive collapse of RC structures subjected to corner column loss, we adopted a novel strengthening scheme (high-performance ferrocement laminate and bonded steel plates) to improve the progressive collapse behavior. Three one-third-scale RC sub-assemblages were constructed and tested to investigate the effectiveness of this strengthening method: control sub-assemblage, beam-strengthened sub-assemblage, and slab-strengthened sub-assemblage. The results demonstrate that beam and slab strengthening schemes can improve the static load-carrying capacity, dynamic resistance, energy dissipation, and ductility of the sub-assemblage. Moreover, the slab-strengthening scheme altered the failure modes of the beams and slabs, significantly increasing the ductility of the sub-assemblage. Consequently, the slab-strengthening scheme exhibited superior performance to the beam-strengthening scheme. Based on the energy conservation theory, the ultimate point of the sub-assemblages with a lost corner column was redefined. Furthermore, theoretical models were proposed and validated to predict the yield, peak, and ultimate loads. •A novel strengthening scheme is used to mitigate progressive collapse.•The slab strengthening scheme modifies the failure modes of beams and slabs.•The ultimate point of the sub-assemblage under loss of a corner column is redefined.•Analytical models are proposed to predict the yield, peak, and ultimate loads.